EXPLORING THE ROLE OF IDEATIONAL FORCES IN INDO-PAK RELATIONS (Journal of Contemporary Studies, 2017)
Abstract The article explores the construction of relations between India and Pakistan with regard to the intangible ideational forces, which add to the material side of the equation. It examines the role of ideational forces in shaping the identity, security dynamics and political relations between the two countries. The analysis detects whether the underlying factor of the conflict can be attributed to the prevalent discourse, inspired by ideology, history and concomitant with identity. Speech acts are rather important in terms of relations between countries; where a change in rhetoric may have an impact on the progression of ties. A critical discourse analysis reveals the varied ways in which the ideational factors of religion and historical experiences come into play in the states’ discourse, the media narrative and the non-state actors’ narrative. Analysing the ideational aspect of discourse is essential; as these narratives take the shape of policy decisions and state behaviour; they generate a continuous cycle of mistrust and animosity amid both the countries.